National Wealth and Gender Inequality in Entrepreneurship: A Paradox in High-Income Economies - Rim Menouar (International Journal of Scientific Research and Innovative Studies, 2025)
This article investigates a paradox identified in the Global Entrepreneurship Monitor (GEM) 2024/2025 data: despite having more developed institutions and greater national wealth, high-income economies often exhibit wider gender gaps in entrepreneurial participation than their lower-income counterparts. Using comparative data from 51 countries, the study analyzes two key indicators—Total Early-stage Entrepreneurial Activity (TEA) by gender and national expert assessments of women’s access to entrepreneurial resources. The results show that nine of the fourteen widest gender gaps in TEA are found in high-income economies, many of which also rate poorly in perceived resource access for women. In contrast, some middle- and low-income countries demonstrate narrower gender disparities, often attributed to necessity-driven entrepreneurship and informal support mechanisms. Grounded in institutional theory and feminist economics, this research highlights the disconnect between formal inclusion and functional equity, arguing that policies framed as gender-neutral may fail to address systemic barriers. The paper calls for equity-based policy interventions—such as gender-lens investment, dedicated mentorship platforms, and targeted support—that can correct for deeply embedded social and institutional biases. Ultimately, the study contributes to both theoretical and policy debates by underscoring the need for context-sensitive, inclusive entrepreneurial ecosystems. Keywords Gender inequality, entrepreneurship, high-income economies, institutional theory, feminist economics, access to resources, Global Entrepreneurship Monitor